2019
DOI: 10.1093/annonc/mdz018
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival and updated progression-free survival outcomes in a randomized phase II study of combination cediranib and olaparib versus olaparib in relapsed platinum-sensitive ovarian cancer

Abstract: Background: Olaparib is a poly(ADP-ribose) polymerase inhibitor and cediranib is an oral anti-angiogenic. In the primary analysis of this phase II study, combination cediranib/olaparib improved progression-free survival (PFS) compared with olaparib alone in relapsed platinum-sensitive ovarian cancer. This updated analysis was conducted to characterize overall survival (OS) and update PFS outcomes.Patients and methods: Ninety patients were enrolled to this randomized, open-label, phase II study between October … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(119 citation statements)
references
References 12 publications
5
113
0
1
Order By: Relevance
“…21 The most striking benefit of bevacizumab comes when one separates the balanced backbones of the AURELIA results, which demonstrated an improvement in PFS from 3.9 months to 10.4 months (hazard ratio [HR], 0.46) with the addition of bevacizumab to weekly paclitaxel. Similarly strong results were observed in the phase 2 trial of the addition of the VEGF receptor inhibitor cediranib to olaparib for women with platinumsensitive disease 22,23 ; the definitive phase 3 NRG GY004 trial currently is maturing and the results are expected this year. Both the Gynecologic Oncology Group (GOG)-0213 trial and the initial trial of the combination of cediranib and olaparib have demonstrated a trend and/or effect of the addition of the angiogenesis inhibitor for overall survival (HR, 0.83 [P = .056] and HR, 0.64 [P = .11], respectively).…”
Section: Novel Combinations Targeting the Tumor And Tumor Microenviromentioning
confidence: 58%
See 2 more Smart Citations
“…21 The most striking benefit of bevacizumab comes when one separates the balanced backbones of the AURELIA results, which demonstrated an improvement in PFS from 3.9 months to 10.4 months (hazard ratio [HR], 0.46) with the addition of bevacizumab to weekly paclitaxel. Similarly strong results were observed in the phase 2 trial of the addition of the VEGF receptor inhibitor cediranib to olaparib for women with platinumsensitive disease 22,23 ; the definitive phase 3 NRG GY004 trial currently is maturing and the results are expected this year. Both the Gynecologic Oncology Group (GOG)-0213 trial and the initial trial of the combination of cediranib and olaparib have demonstrated a trend and/or effect of the addition of the angiogenesis inhibitor for overall survival (HR, 0.83 [P = .056] and HR, 0.64 [P = .11], respectively).…”
Section: Novel Combinations Targeting the Tumor And Tumor Microenviromentioning
confidence: 58%
“…Both the Gynecologic Oncology Group (GOG)-0213 trial and the initial trial of the combination of cediranib and olaparib have demonstrated a trend and/or effect of the addition of the angiogenesis inhibitor for overall survival (HR, 0.83 [P = .056] and HR, 0.64 [P = .11], respectively). 20,23 To our knowledge, no overall survival advantage of the addition of antiangiogenic therapy has otherwise been demonstrated to date for ovarian cancer. Another tumor microenvironment target is the immune microenvironment.…”
Section: Novel Combinations Targeting the Tumor And Tumor Microenviromentioning
confidence: 96%
See 1 more Smart Citation
“…That this combination was effective even in PARPi-resistant cases may be due to cediranib-mediated suppression of BRCA1/2 and RAD51 expression, both indirectly through induction of hypoxia, and directly through transcriptional repression [117]. In a similar patient population of germline BRCAwt platinum sensitive recurrent EOC, combination cediranib/olaparib had greater activity compared to olaparib alone in post-hoc analyses of a phase II trial, prolonging median PFS from 5.7 months to 23.7 months (p = 0.002) and median OS from 23.0 months to 37.8 months (p = 0.047) [118]. In prespecified subset analysis in a subsequent phase III trial (GY-004), however, the population with germline BRCAwt platinum sensitive recurrent EOC performed comparably to platinum-based chemotherapy (ORR 64% cediranib/olaparib versus 72% chemotherapy; HR 0.97, 95% CI 0.73-1.30) [119].…”
Section: Parpi and Anti-angiogenic Agentsmentioning
confidence: 96%
“…In an exploratory subgroup analysis, patients that were germline BRCA wild-type seemed to potentially benefit more from this treatment, with progression-free survival and overall survival improvement only seen in that subgroup of patients. 36 Nevertheless, grade ≥3 adverse events were reported by 70% of patients in the combination arm, mainly hypertension, diarrhea, and fatigue. Our group assessed the combination of olaparib (300 mg, tablets twice daily) and cediranib (20 mg once daily) in a single-arm phase II study in patients having progressed to prior PARPi treatment, regardless of platinum sensitivity, and showed a signal of activity.…”
Section: Parp Inhibitors In Combination With Other Agentsmentioning
confidence: 99%